2019
DOI: 10.1002/jbio.201900123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gravid mosquitoes from changes in spectral and polarimetric backscatter cross sections

Abstract: Improving the survey of mosquito populations is of the utmost importance to further enhance mitigation techniques that protect human populations from mosquito‐borne diseases. While mosquito populations are generally studied using physical traps, stand‐off optical sensors allow to study insect ecosystems with potentially better spatial and temporal resolution. This can be greatly beneficial to eco‐epidemiological models and various mosquito control programs. In this contribution, we demonstrate that the gravidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 50 publications
0
34
0
1
Order By: Relevance
“…Recently developed line sensors with higher sample rates could be implemented in lidar systems, which would potentially improve the frequency analysis and classification. Additional spectral- and polarization bands have been shown to enable the classification of similar species [ 22 ] and the distinction of gravid from non-gravid females [ 50 ] in the laboratory, despite the overlapping WBF distributions of the groups. Radial activity maps could be obtained by scanning the laser beam slowly over a field.…”
Section: Discussionmentioning
confidence: 99%
“…Recently developed line sensors with higher sample rates could be implemented in lidar systems, which would potentially improve the frequency analysis and classification. Additional spectral- and polarization bands have been shown to enable the classification of similar species [ 22 ] and the distinction of gravid from non-gravid females [ 50 ] in the laboratory, despite the overlapping WBF distributions of the groups. Radial activity maps could be obtained by scanning the laser beam slowly over a field.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning flying insects, mostly fruitflies were detected by using opto-electronic sensors in McPhail traps. They had an evolution from the simpler infrared beams to the more sophisticated ones (see in Table 1: Potamitis, Rigakis, Vidakis, Petousis and Weber [20]), which was based on the attributes of arthropods' wingbeats [21,28,29]. The species selectivity is a very big step in automatic monitoring of arthropods, since both practical IPM experts and field ecologists are interested in target pest species or the population dynamics of a particular species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the body and wings of insects display distinct degrees of linear polarization (DoLP) from various aspects and scattering angles [28–30]. We use the definition of DoLP: DoLP=normalIcoIco+Ide. …”
Section: Methodsmentioning
confidence: 99%